Oxford Understanding History 2 - Ismat Riaz (Karachi: Oxford University Press., 2024)
Oxford Understanding History 2 continues the exploration of world history, focusing on key events, civilizations, and figures from medieval to early modern periods. The textbook engages students through detailed narratives, timelines, and maps, helping them understand the development of societies, cultural exchanges, and significant historical milestones. With an emphasis on critical thinking and analysis, students are encouraged to evaluate historical sources, understand cause and effect, and draw connections between historical events and modern-day contexts. This book builds on the foundation established in the previous volume, preparing students for deeper inquiry into global history and fostering a greater appreciation for the past.